Development of dried rice noodles fortified with β- carotene from differently processed carrots (Daucus carota L.) - Ismail, Hamidah (2019)
The trend towards consuming foods fortified with fruits and vegetables is escalating due to the increasing consumer awareness on functional foods which include fortified rice noodles. However, food processing such as dried rice noodle making often involves high temperature and high moisture that can affect the stability of fruit and vegetable nutrients such as ß-carotene from carrot. This study was conducted to determine the physico-chemical properties of 3 differently processed carrot preparations namely carrot puree (CP) as a control, oven dried carrot powder (ODCP) and spray dried carrot powder (SDCP), the retention and storage stability of β–carotene in rice noodles fortified with these preparations post extrusion, and β-carotene retention as well as the physico-chemical properties of the aforementioned fortified noodles after cooking. Each processed carrot preparation at various levels (5%, 10% or 15%) was mixed with rice flour and tapioca starch blend (80:20) and the moisture content of the mixture (extrusion feed) was adjusted to 30% before extrusion at 80 °C, 100 °C, 100 °C, 100 °C for zones 1, 2, 3 and 4 of the extruder barrel, respectively. The feed rate was set at 20 rpm with a screw speed of 60 rpm. The fortified rice noodles were dried at 30 °C for 16 h and then analyzed for ß-carotene content, retention of ß-carotene, and colour. In addition, the physico-chemical properties of CP, ODCP and SDCP were also examined. The results showed that SDCP exhibited the lowest moisture content (4.09%) and the lowest hygroscopicity (15.92%) while ODCP had the lowest water activity (0.37), highest ß-carotene content (159.48 mg/100g) and highest redness value. ß-carotene content of the noodles increased as level of fortification with CP, ODCP and SDCP increased. Dried rice noodle containing 15% ODCP had the highest ß-carotene content (5.74 mg/100g) and redness value (21.06) compared to the other fortified dried rice noodles while 5% CP noodle had a significantly higher ß-carotene retention (63.45%) post extrusion compared to the other fortified rice noodles. The redness value of the noodles was positively correlated with their ß-carotene content. Storage stability and degradation kinetics of ß-carotene in the dried rice noodles were assessed under conditions of with or without light and oxygen at room temperature or 40 ºC. Presence of oxygen, exposure to light and elevated temperature of 40 ºC were found to increase ß-carotene degradation. Half-life of ß-carotene in noodles containing CP was the highest (25 - 103 weeks) followed by that in noodles containing SDCP (8 - 19 weeks) and ODCP (8 - 15 weeks) for all levels of fortification and storage conditions. Cooking quality, textural properties, sensory properties, ß-carotene retention, ß-carotene content and colour of fortified noodles post cooking were also studied. All noodle rehydration and cooking loss values were in the acceptable range of 167.83% - 207.29% and 5.70% - 11.20%, respectively. In terms of textural qualities, rice noodles containing 15% ODCP and 15% SDCP had significantly lower hardness, gumminess and chewiness compared to the other noodles. For sensory evaluation, both of these samples were not significantly different in terms of their flavour, texture and overall acceptability except for their appearance. However, rice noodles containing 15% ODCP exhibited a significantly higher ß-carotene retention (51.90%), ß-carotene content (2.09 mg/100g) and redness value (8.03) post cooking. In conclusion, 15% ODCP noodle was chosen to be the best fortified rice noodle due to its high β- carotene content, high retention of β-carotene post cooking, most orange in colour and acceptability by the sensory panelists.